Episcopalians and Race : Civil War to Civil Rights - Shattuck, Gardiner H. (Book collections on Project MUSE., 2000)
Meeting at an African American college in North Carolina in 1959, a group of black and white Episcopalians organized the Episcopal Society for Cultural and Racial Unity and pledged to oppose all distinctions based on race, ethnicity, and social class. They adopted a motto derived from Psalm 133: """"Behold, how good and joyful a thing it is, for brethren to dwell together in unity!"""" Though the spiritual intentions of these individuals were positive, the reality of the association between blacks and whites in the church was much more complicated. Episcopalians and Race examines the often amb.